CoenzymeQ10-Induced Activation of AMPK-YAP-OPA1 Pathway Alleviates Atherosclerosis by Improving Mitochondrial Function, Inhibiting Oxidative Stress and Promoting Energy Metabolism - Xie, Tianqi; Wang, Changyuan; Jin, Yue; Meng, Qiang; Liu, Qi; Wu, Jingjing; Sun, Huijun (Frontiers in Pharmacology, 2020)
Atherosclerosis (AS) is an excessive chronic inflammatory hyperplasia caused by the damage of vascular endothelial cell morphology and function. Changes in mitochondrial internal conformation and increase of reactive oxygen species (ROS) can lead to energy metabolism disorders in mitochondria, which further affects the occurrence of atherosclerosis by impairing vascular endothelial function. Coenzyme Q10 (CoQ10) is one of the components of mitochondrial respiratory chain, which has the functions of electron transfer, reducing oxidative stress damage, improving mitochondrial function and promoting energy metabolism. The main purpose of this study is to investigate the protective effects of CoQ10 against AS by improving mitochondrial energy metabolism. Both in high fat diet (HFD) fed APOE-/- mice and in ox-LDL-treated HAECs, CoQ10 significantly decreased the levels of TG, TC and LDL-C and increased the levels of HDL-C, thus playing a role in regulating lipid homeostasis. Meanwhile, CoQ10 decreased the levels of LDH and MDA and increased the levels of SOD and GSH, thus playing a role in regulating oxidation level. CoQ10 also inhibited the over-release of ROS and increased ATP content to improve mitochondrial function. CoQ10 also decreased the levels of related inflammatory factors (ICAM-1, VCAM-1, IL-6, TNF-α and NLRP3). In order to study the mechanism of the experiment, AMPK and YAP were silenced in vitro. The further study suggested AMPK small interfering RNA (siRNA) and YAP small interfering RNA (siRNA) affected the expression of OPA1, a crucial protein regulating the balance of mitochondrial fusion and division and decreased the therapeutic effects of CoQ10. These results indicated that CoQ10 improved mitochondrial function, inhibited ROS production, promoted energy metabolism and attenuated AS by activating AMPK-YAP-OPA1 pathway. This study provides a possible new mechanism for CoQ10 in the treatment of AS and may bring a new hope for the prevention and treatment of AS in the future.